Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
$x-\frac{31}{15}.\frac{26}{47}=\frac{-57}{15}.\frac{31}{47}-\frac{31}{15}:\frac{-141}{31}$
$x=\frac{-57}{47}.\frac{31}{15}-\frac{31}{15}.\frac{-31}{141}+\frac{31}{15}.\frac{26}{47}$
$x=\frac{31}{15}(\frac{-57}{47}-\frac{-31}{141}+\frac{26}{47})$
$x=\frac{31}{15}.\frac{-62}{141}=\frac{-1922}{2115}$
\(x.\frac{2}{3}+x.\frac{1}{5}=\frac{26}{15}\)
\(x.\left(\frac{2}{3}+\frac{1}{5}\right)=\frac{26}{15}\)
\(x.\frac{13}{15}=\frac{26}{15}\)
\(x=\frac{26}{15}:\frac{13}{15}\)
vậy x=2
hok tốt nha!
v
\(x.\frac{2}{3}+x.\frac{1}{5}=\frac{26}{15}\)
\(x.\left(\frac{2}{3}+\frac{1}{5}\right)=\frac{26}{15}\)
\(x.\frac{13}{15}=\frac{26}{15}\)
\(x=\frac{26}{15}:\frac{13}{15}\)
\(x=2\)
Nhầm, làm lại nhé!
\(\frac{x}{13}+\frac{15}{26}=\frac{46}{52}\)
\(\frac{x}{13}+\frac{15}{26}=\frac{23}{26}\)
\(\frac{x}{13}=\frac{23}{26}-\frac{15}{26}\)
\(\frac{x}{13}=\frac{23}{26}-\frac{15}{26}\)
\(\frac{x}{13}=\frac{4}{13}\)
\(\Rightarrow x=\frac{13.4}{13}=4\)
Vậy \(x=4\)
a,(x-15)-75=0
x-15 =75
x =75+15
x =90
b,72-(6.x+5)=55
6.x+5=72-55
6.x+5=17
6.x=17-5
6.x=12
x=12:6
x=2
c,575-(6.x+70)=445
6.x+70=575-445
6.x+70=130
6.x=130-70
6.x=60
x=60:6
x=10
d,(x-34).15=0
x-34=0
x=34
e,15+(18-x)=26
18-x=26-15
18-x=11
x=18-11
x=7
g,(x-5):16=2
x-5=2.16
x-5=32
x=32+5
x=37
15/26 + x/16 = 46/52
x/16 = 46/52 - 15/26
x/16 = 1/4
x/16 = 4/16
Suy ra: x = 4
Vậy x = 4
\(\frac{15}{26}+\frac{x}{16}=\frac{46}{52}\)
\(\Rightarrow\frac{x}{16}=\frac{45}{52}-\frac{15}{26}\)
\(\Rightarrow\frac{x}{16}=\frac{4}{13}\Rightarrow\frac{64}{208}=\frac{x}{16}=\frac{64}{208}=\frac{x}{208}\Rightarrow x=64\)
=26/15;-26/15 nha bạn